DEVELOPING DIGITAL WORKSHEET BY USING WIZER.ME FOR TEACHING LISTENING SKILL TO THE TENTH GRADE STUDENTS IN SMK NEGERI 7 MEDAN - Elly Anggriani Nasution; Sumarsih Sumarsih; Nora Ronita Dewi (TRANSFORM : Journal of English Language Teaching and Learning, 2020)
Digital worksheet, as the one of learning tools that is used to involve the students to works actively during teaching and learning process, should be developed based on students’ need. Digital worksheet in listening skill with scientific approach has not applied. A good digital worksheet must be fulfilled criteria of valid, practical and effective. The aim of this study was to develop English Listening Digital Worksheet for Grade X for Vocational school Students. This study was conducted by using Research and Development (R&D) design through six stages; need analysis, planning, designing digital worksheet, materials evaluation, revising (final product). The subject of the study was Grade X of Hospitality Major at SMK Negeri 7 Medan. The data were gathered by conducting interview to English teacher and distributing questionnaire to 1 class grade X consists of 36 students to get the students’ needs. The interview and questionnaire results prove that the students needs of English Listening Digital Worksheet appropriate with the Hospitality Major context. The product has been validated by experts. The result of the product was the digital worksheet combined with the Wizer.me platform.Keywords: english listening digital worksheet, Wizer.me, research and development (R&D)